In the Scattered Fields of Memory: Unofficial Live Music Venues, Intangible Heritage, and the Recreation of the Musical Past. (November 2016) - Bennett, Andy; Rogers, Ian
The live music venue has long been regarded as a space of critical importance in relation to musical experience. Like music artists themselves, venues often come to embody the zeitgeist of a particular genre or era. Liverpool's Cavern, New York's CBGB's, and Brisbane's Cloudland are but three examples of an ever-growing list of live music venues (closed down, demolished, renamed) achieving iconic status due to a connection with important and galvanizing moments in music history. Significant in this are the ways in which collective memories become textured by particular venues and how memory works to forge strong collective associations between former audiences. Drawing on theoretical frameworks utilized in space and place research and memory studies, this article will investigate the significance of unofficial, unlicensed music venues and the way in which the memory of these particular sites constitute a potent form of intangible cultural heritage in contemporary society.